Study guides

☆☆

Q: What is 1 divided by x divided by 2 divided by y?

Write your answer...

Submit

Still have questions?

Related questions

Y / (2+x)If x = -1 and y=2, thenY / (2+x) = 2/(2-1) = 2/1 = 2

wat is the whole problem that actually it is 42

-1

y=(x+2)/(x+10) xy+10y=x+2 xy-x=2-10y x(y-1)=2-10y x=(2-10y)/(y-1)

Divide the numerator by the denominator. For example, 1/2: 1 divided by 2 is 50% In algebra form: x/y: x divided by y= percent the "/" symbol actually means "divided by" so when you say 1/2, your actually saying 1 divided by 2

It is x^2 + xy + y^2

if INVERSELY proportional then y = 1/X^2 ( that is, 1 divided by x squared) If X doubles then X SQUARED increases as 2 x 2 = 4 times SINCE Y = 1/x^2 then Y DECREASES 4 times

y = x / (x^2 + 2x + 1) The horizontal asymptote is y = 0

X = 17.7 + 0.1y

y = square root of x y = x(1/2) y' = (1/2)x(1/2 - 1) y' = (1/2)x(-1/2) y' = (1/2)(square root of x)

X^4 divided by Y^2

When dividing fractions, multiply by the inverse of the fraction.That is, a/b divided by x/y = a/b times y/x = ay/bxFor example,2/5 divided by 3 = 2/5 x 1/3 = 2/152/5 divided by 1/3 = 2/5 x 3/1 = 6/55 divided by 3 = 5/1 x 1/3 = 5/35 divided by 1/3 = 5/1 x 3/1 = 15/1 (= 15)

If [ y = x + 2 ], then x is not -1 when y = 5.If [ y = x + 2 ],then when x = -1, y = 1,and when y = 5, x = 3.

y = -2x² + x y = -2 [ x² - (x/2) ] y = -2 [ x² - (x/2) + (1/4) ] + (1/2) y = (1/2) - 2[ x - (1/2) ]² ≤ (1/2) Hence, the Range of y is : -∞ < y ≤ (1/2). It can be written as the interval ( -∞, 1/2 ]. ........ Ans. _____________________________________ Happy To Help ! _____________________________________

let y= xsqrt(x) -1 y= x^(3/2) -1 ---- since xsqrt(x) is the same as x^(3/2) y' = (3/2) x^(3/2-1) y' = (3/2) x^(1/2) y'' = (3/2) (1/2) x^(1/2-1) y'' =(3/2)(1/2) x^(-1/2) y'' = 3/4x^(1/2) y'' = 3 / 4sqrt(x)

1/x = y x = 1/y

y = 3√x y = 3x^(1/2) y' = 3(1/2)x^(1/2 -1) y'= (3/2)x^(-1/2) y' = 3/[2x^(1/2)] y' = 3/(2√x)

X divided by -Y is the same as -X divided by Y. Or - (X/Y)

y = x + 2 y = -x + 4 x + 2 = -x + 4 2x + 2 = 4 2x = 2 x = 1 y = x + 2 y = 1 + 2 y = 3 (1, 3)

Eq 1: + y= 5 Eq 2: x = y + 1 substitute y + 1 for x in equqtion 1 y+1 + y = 5 2y + 1 = 5 2 y = 4 y = 2 substitute 2 for y in eq 2 x = 2 + 1 x = 3

(1/x) - (1/y) = (1/z) Get the left-hand side over a common denominator:- (y-x)/xy = 1/z Take the reciprocal of both sides:- z = xy / (y-x)

y=f(x)= x(2x+y)=7 f(x)=2x^2 +xy -7 = 0 y=2x^2 +xy -7 y-xy -7 + 2x^2 = 0 y(1-x)=2x^2-7 y=(2x^2-7) / (1-x) Excuse the working. Y equals 2 X squared minus 7 all divided by 1-X

unless you have something to plug in the answer will be y/x or y divided by x or y over x

x + y = 1 therefore x = 1 - y. 2x - y = -2 substituting x = 1 - y in this equation gives 2*(1 - y) - y = -2 That is, 2 - 2y - y = -2 or -3y = -4 => y = 4/3. Then x = 1 - y => x = 1 - 4/3 = -1/3. Therefore, the solution is (x, y) = (-1/3, 4/3).

X/3+Y There is no answer unless its equal to something X/3+Y=0 for example, or you have a value for the variables (1)/3+(2).